2021
DOI: 10.1038/s41537-021-00165-0
|View full text |Cite|
|
Sign up to set email alerts
|

Multivariate pattern analysis of brain structure predicts functional outcome after auditory-based cognitive training interventions

Abstract: Cognitive gains following cognitive training interventions are associated with improved functioning in people with schizophrenia (SCZ). However, considerable inter-individual variability is observed. Here, we evaluate the sensitivity of brain structural features to predict functional response to auditory-based cognitive training (ABCT) at a single-subject level. We employed whole-brain multivariate pattern analysis with support vector machine (SVM) modeling to identify gray matter (GM) patterns that predicted … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…In this first-of-its-kind report, we now deliver robust evidence revealing the caudate anterior head division is one region that contributes to the neural pathophysiology underlying hallucinations in schizophrenia. We have previously shown that it is possible to predict treatment response at the individual level using structural MRI and resting-state fMRI ( Hinkley et al, 2022 ; Kambeitz-Ilankovic et al, 2021 ; Haas et al, 2021b ). The next step in a larger sample would be to investigate the predictive accuracy of treatment response to deep brain stimulation for improving hallucination severity at the individual level using machine learning approaches based on resting state connectivity metrics and clinical measures, such as the PANSS, Psychotic Symptoms Rating Scales (PSYRATS) ( Haddock et al, 1999 ) and Auditory Vocal Hallucination Rating Scale (AVHRS) ( Bartels-Velthuis et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this first-of-its-kind report, we now deliver robust evidence revealing the caudate anterior head division is one region that contributes to the neural pathophysiology underlying hallucinations in schizophrenia. We have previously shown that it is possible to predict treatment response at the individual level using structural MRI and resting-state fMRI ( Hinkley et al, 2022 ; Kambeitz-Ilankovic et al, 2021 ; Haas et al, 2021b ). The next step in a larger sample would be to investigate the predictive accuracy of treatment response to deep brain stimulation for improving hallucination severity at the individual level using machine learning approaches based on resting state connectivity metrics and clinical measures, such as the PANSS, Psychotic Symptoms Rating Scales (PSYRATS) ( Haddock et al, 1999 ) and Auditory Vocal Hallucination Rating Scale (AVHRS) ( Bartels-Velthuis et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…15 Moreover, recent studies have explored the potential of machine learning to predict further important clinical end-points for people on the psychosis spectrum, such as the development of poor psychosocial functioning. 16,17 To use such models in clinical practice, it is of utmost importance to ensure both high robustness and generalisability – a prerequisite that has only recently started to be addressed. 18,19 An equally important prerequisite for the deployment of prediction algorithms in clinical settings is their compliance with ethical principles.…”
Section: Psychosis Risk States and Prediction Modelsmentioning
confidence: 99%